Effects of nitric oxide system and osmotic stress on Aquaporin-1 in the postnatal heart - Netti, Vanina Alejandra (2016)
Aquaporin-1 (AQP1) is expressed in the heart and its relationship with NO system has not been fully explored. The aims of this work were to study the effects of NO system inhibition on AQP1 abundance and localization and evaluate AQP1 S-nitrosylation in a model of water restriction during postnatal growth. Rats aged 25 and 50 days (n = 15) were divided in: R: water restriction; C: water ad libitum; RL: L-NAME (4 mg/kg day) + water restriction; CL: L-NAME + water ad libitum. AQP1 protein levels, immunohistochemistry and S-nitrosylation (colocalization of AQP1 and S-nitrosylated cysteines by confocal microscopy) were determined in cardiac tissue. We also evaluated the effects of NO donor sodium nitroprusside (SNP) on osmotic water permeability of cardiac membrane vesicles by stopped-flow spectrometry. AQP1 was present in cardiac vascular endothelium and endocardium in C and CL animals of both ages. Cardiac AQP1 levels were increased in R50 and RL50 and appeared in cardiomyocyte plasma membrane. No changes in AQP1 abundance or localization were observed in R25, but RL25 group showed AQP1 presence on cardiomyocyte sarcolemma. AQP1 S-nitrosylation was increased in R25 group, without changes in the 50-day-old group. Cardiac membrane vesicles expressing AQP1 presented a high water permeability coefficient and pretreatment with SNP decreased water transport. Age-related influence of NO system on AQP1 abundance and localization in the heart may affect cardiac water homeostasis during hypovolemic state. Increased AQP1 S-nitrosylation in the youngest group may decrease osmotic water permeability of cardiac membranes, having a negative impact on cardiac water balance.